Optical tomography : transmitter and receiver circuit preparation - Mohd Muji, Siti Zarina; Abdul Rahim, Ruzairi; A. Johnson, David; Rahiman, Mohd Hafiz Fazalul; Mohamad, Elmy Johana; Amani, Hudabiyah Arshad; Abdul Sahib, Mohd Fadzli (Penerbit UTM Press, 2011)
This paper focuses on the factors that need to be considered while making the decision for transmitter, receiver and other parts that are needed in the preparation for the optical tomography circuit. The major discussion is on the selection of transmitter and receiver’s sensor, operational amplifier, and the arrangement of components in the circuit. This paper provides guidance on how to select the appropriate component and rearrange them to construct a good and functional circuit.